Padua Score and D-dimer for Pulmonary Embolism Exclusion in the Elderly - Ramon Cohen; Shay Nemet; Marina A. Fradkin; Tal Schiller; Alena Kirzhner; Haitham Abu Khadija; Meital Deitch; Daniel Elbirt (Rambam Maimonides Medical Journal)
Purpose: This study was aimed at identifying biomarkers that could help exclude pulmonary embolism (PE) in patients aged 65 years and older, considering age-related challenges such as atypical clinical presentations and the presence of comorbidities.